Internet of Things (IoT) and Smart Agriculture: With Reference to Applications and Emerging Concern - Paul, P. K.; Sinha, R. R.; Aithal, P. S.; Saavedra, Ricardo; Aremu, Bashiru; S. Mewada (Asian Journal of Electrical Sciences, 2020)
Agricultural Informatics is one of the important emerging domains gaining popularity in recent years. This is simply the application of Information Technology and Computing in Agriculture and allied activities. This is also the combination of ‘Agricultural Science’ and ‘Informatics or Information Science’. This emerging as an interdisciplinary subject and provides solutions for the smarter agriculture and advancement of the agricultural sectors. It is connected with various kinds of information and technological tools. In the recent past, various IT components have emerged and all these are responsible for the agricultural activities leading to cultivation; its enhancement, productivity, quality, cleanliness, efficiency, post agricultural activities. The Agricultural Informatics is responsible for the design, development, management and implementation of the advanced and intelligent agricultural systems, that may call as ‘Smart Agriculture’ or it may be called as ‘Digital Agriculture’. For the creation of such agricultural systems, various emerging Information Technological tools and technologies are emerging and among these important are Cloud Computing, Big Data, Internet of Things (IoT), Robotics & Artificial Intelligence, Human Computer Interaction, etc. Internet of Things (IoT) is applicable in designing and development of healthy and intelligent information systems that are connected with the internet and similar systems. IoT is responsible for various kinds of Agricultural development activities. This paper is conceptual in nature and deals with a brief overview on Agricultural Informatics including evolution, features and role and importance in the concentration of its applications in the creation of ‘Smart Agriculture’ and also emphasized how IoT and similar systems are helpful in promotion of Agricultural activities, intelligent and smarter way. Paper also highlighted about the issues, challenges and concerns on Agricultural Informatics with special reference to its IoT applications in Agriculture towards the promotion of Smart Agriculture.